Rumen fermentation pattern of Barbari kids at different physiological stages under semi-intensive system of production - MAMTA, MAMTA; DUTTA, T K; TRIPATHI, M K (The Indian Journal of Animal Sciences, 2015)
An experiment on 24 goat kids, 8 of each stage of growth (K1, 3–6 month; K2, 6–9 months; K3, 9–12 months) was conducted to study the rumen fermentation pattern of goat kids under semi-intensive system of feeding and management. The semi-intensive system of goat production involved 6 to 8 h daily grazing with feeding of concentrate at 1.5% of live weight, dry roughage (gram straw) ad lib. and green fodder 1,500 g/ animal/ day after grazing. The rumen fluid pH, total-N (mg/dl) and NPN (mg/dl) were similar among kid groups and mean levels were respectively 6.5, 70.81 mg/dl and 39.83 mg/dl. The TCA-ppt-N and NH3-N concentration were lower (p